Recombination Losses Above and Below the Transport Percolation Threshold in Bulk Heterojunction Organic Solar Cells. Issue 18 (13th March 2018) - Yazmaciyan, Aren; Stolterfoht, Martin; Burn, Paul L.; Lin, Qianqian; Meredith, Paul; Armin, Ardalan
Abstract: Achieving the highest power conversion efficiencies in bulk heterojunction organic solar cells requires a morphology that delivers electron and hole percolation pathways for optimized transport, plus sufficient donor:acceptor contact area for near unity charge transfer state formation. This is a significant structural challenge, particularly in semiconducting polymer:fullerene systems. This balancing act in the model high efficiency PTB7:PC70BM blend is studied by tuning the donor:acceptor ratio, with a view to understanding the recombination loss mechanisms above and below the fullerene transport percolation threshold. The internal quantum efficiency is found to be strongly correlated to the slower carrier mobility in agreement with other recent studies. Furthermore, second‐order recombination losses dominate the shape of the current density–voltage curve in efficient blend combinations, where the fullerene phase is percolated. However, below the charge transport percolation threshold, there is an electric‐field dependence of first‐order losses, which includes electric‐field‐dependent photogeneration. In the intermediate regime, the fill factor appears to be limited by both first‐ and second‐order losses. These findings provide additional basic understanding of the interplay between the bulk heterojunction morphology and the order of recombination in organic solar cells. They also shed light on the limitations of widely used transport models below the percolation threshold. Abstract : By varying the fullerene fraction above and below the electron percolation threshold in the model high efficiency OPV system PTB7:PC71BM, the importance of electric‐field‐dependent first‐order losses is shown. The results also shed light on the limitations of widely used and accepted transport models below the percolation threshold of the bulk heterojunction system.